A Postcolonial Political Theology of Care and Praxis in Ethiopia's Era of Identity Politics : reframing hegemonic and fragmented identities through subjective in-betweenness - Molla, Rode (Lanham, Maryland : Lexington Books, an imprint of The Rowman & Littlefield Publishing Group, Inc., 2023)
"The author argues that identity politics eliminates Ethiopians' in-between spaces and identities and defines in-between spaces as political, social, religious, and geographical spaces that enable Ethiopians to co-exist with equity, solidarity, and justice. The elimination of in-between spaces and in-between identities creates either-or class, religious, ethnic, and gender categories. Therefore, the author proposes an in-between theology that invites Ethiopians to a new hybrid way of being to resist fragmented and hegemonic identities. The author claims that postcolonial discourse and praxis of in-between pastoral care disrupts and interrogates hegemonic definitions of culture, home, subjectivity, and identity. On the other hand, in-between pastoral care uses embodiment, belonging, subjectivity, and hybridity as features of care and praxis to create intercultural and intersubjective identities that can co-construct and co-create in-between spaces. In the in-between spaces, Ethiopians can relate with the Other with intercultural competencies to live their difference, similarity, hybridity, and complexity"--
Includes bibliographical references and index.
Description based on print version record and CIP data provided by publisher.
Keywords: Pastoral theology -- Ethiopia; Political theology -- Ethiopia; Identity politics -- Ethiopia; Religion and politics -- Ethiopia; Ethnic relations -- Ethiopia; Postcolonialism -- Ethiopia